Determinants of capital structure: an empirical study of manufacturing firms in India. Issue 6 (13th November 2017) - Sofat, Rajni; Singh, Sukhdev
Abstract : Purpose: The purpose of this paper is to explore the most significant determinants of capital structure of manufacturing firms in India and to investigate whether the capital structure models derived from foreign research provide convincing explanations for capital structure decisions of Indian firms by using multiple regression model. Design/methodology/approach: Different conditional theories of capital structure like trade off theory, pecking order theory and agency theory are reviewed to formulate testable propositions concerning determinants of capital structure of manufacturing firms. Multiple regression model and correlation matrix have been used as statistical tools to investigate the most significant determinants of capital structure of manufacturing firms in India with the help of SPSS Software for a sample of top 100 manufacturing firms listed in BSE. Findings: The results suggest that variables like asset composition, business risk and return on assets are positively related to debt ratio whereas firm size and debt service capacity are negatively related to debt ratio. The asset composition, business risk and return on assets appear to be significant determinants of capital structure, while firm size and debt service capacity are insignificant determinants. Research limitations/implications: The findings of this study are consistent with predictions of trade off, pecking order and agency theory of finance which helps in understanding financing behaviour of firms in India. Practical implications: This study has laid some ground work to explore the determinants of capital structure of Indian firms upon which a more detailed evaluation could be based. Furthermore, empirical findings should help corporate managers to make optimal capital structure decisions. Originality/value: To the authors' knowledge, this study is the first that explores the most significant determinants of capital structure of manufacturing firms in India by using the most recent data. Moreover, this study also confirms that same factors affect the capital structure decisions of firms in developing countries as identified for firms in developed economies.